"I'm afraid of cops:" black protesters' and residents' perceptions of policing in the United States. Issue 3 (2nd October 2021) - Cobbina-Dungy, Jennifer
Abstract: Proactive policing strategies produce a wide range of harms to African Americans. Research on attitudes towards police show that citizen distrust is more widespread among Blacks than Whites. However, we know less about how gender intersects with race and neighborhood context in determining whether and why Black people fear the police. Here, I build from the insights of previous research by providing a contextual examination of the gendered nature of fear of the police among Black protesters and residents of Ferguson, Missouri and Baltimore, Maryland. Drawing from a larger qualitative study of race, policing, and protests following Michael Brown's and Freddie Gray's deaths, I examine 155 Black men's and women's accounts of why they do or do not fear the police. Policy implications are discussed, along with concrete recommendations for reducing anti-Black racism in police policy and practice.